1980
DOI: 10.1115/1.3138195
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of the Point of Maximum Oscillations in Cuff Pressure in the Indirect Measurement of Blood Pressure—Part II

Abstract: When measuring blood pressure indirectly, oscillations in the cuff pressure are observed. The cuff pressure for which these oscillations reach a maximum and its relationship to the true mean arterial pressure was investigated using a simple one-dimensional theoretical model of the cuff-arm-artery system. Results from this model indicate that the cuff pressure for maximal oscillation is strongly dependent on compression chamber air volume, pulse pressure, and arterial elasticity. Parallel experimental studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
4

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(52 citation statements)
references
References 0 publications
1
47
0
4
Order By: Relevance
“…Prior studies have suggested that variations in arterial wall stiffness and arterial pulse pressure cause errors in systolic and diastolic blood pressure estimates using the oscillometric method [4,14,15]. Hence, these variables were studied explicitly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies have suggested that variations in arterial wall stiffness and arterial pulse pressure cause errors in systolic and diastolic blood pressure estimates using the oscillometric method [4,14,15]. Hence, these variables were studied explicitly.…”
Section: Resultsmentioning
confidence: 99%
“…The challenge of creating a satisfactory theoretical treatment of the genesis and interpretation of cuff pressure oscillations has attracted a diverse community of thinkers [4,5,7-10,16]. Nevertheless, specifying a valid method for extracting systolic and diastolic pressures from the envelope of cuff pressure oscillations remains an open problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32,39,97 The oscillations begin at approximately systolic pressure and continue below diastolic (Fig. 1), so that systolic and diastolic pressure can only be estimated indirectly according to some empirically derived algorithm.…”
Section: Basic Techniques Of Blood Pressure Measurementmentioning
confidence: 99%